Morphological and molecular assessment of several cultivars of bread wheat Triticum aestivum L. under different types of irrigation water. (November 2019) - Al-Burki, F R A; Abdel, C G; Majeed, D M; Aoiez, A Q; Afrah Mohammed, A.; Hameed, H
Abstract: The experiment was carried out at the second research station, College of Agriculture, Al-Muthanna University during the winter season 2018-2019, to investigate the performance of four wheat cultivars namely Rasheed, IBA99, Bhooth and Abu Graib subjected K+ supplants to antagonize Na+ effect on growth, yield and genome of four wheat cultivars. Subsequently, varying irrigation water qualities were applied, namely Euphrates river water of 2.4 ds.m-1 electrical conductivity (EC), river water + 400 ppm of K+, saline water of 5 ds.m-1EC, and saline water+ 400 ppm of K+. The results revealed the superiority of K+ addition to river and salty water through irrigation substantially antagonized Na+ adversity. Where K+ improved the performance of river water and salty water in plant height (70.71and 72.25 cm, respectively) and leaf area (28.29, and 24.41cm2, respectively) as they compared to river water without K+ (63.83 cm and 21.87 cm2, respectively). IBA99 wheat cultivars showed superiority over others, since it gave the highest plant height (70.375 cm), 1000 seed weights (32.583 g) and grain number per spike (55.475), then comes in the second order Rasheed, as it gave the higher values in plant height (74.41 cm), 1000 seed weight (33.33 g), and spike length (14.816 cm), as compared to Bhooth and Abu Graib cultivars. Then Abu Graib comes in the third order, followed by the worst Bhooth cultivar. Rasheed X + river water + k+was the most potent dual combination, since it showed the highest plant height (78.66 cm), leaf area (35.05 cm2. - 1), and weight of 1000 grain reached (37.33 g). IBA99 + salt water + k+ combination manifested superiority in the grains number of spike which gave 61.36 g. Molecular analysis results in agreement with the those of the morphological analysis by the appearance of TaHKT2;2 gene bands very clear in the Rasheed cultivar, the DNA size of the gene reached 500 nucleotides. Indicating the clear genetic expression of the gene in the varieties (except Abu Graib), especially for the Rasheed cultivar with a combination (Rasheed with salt water + K+), and the positive role played by potassium ion in reducing the harmful effect of sodium ions, Rasheed in the breeding programs of wheat crop to the salt stress tolerance through the hybridization because of its superiority over the rest of the local varieties.